A survey on set-membership filtering for networked control systems under communication protocols. Issue 1 (1st January 2018) - Li, Xuerong; Dong, Hongli; Han, Fei; Li, Jiahui
ABSTRACT: In recent years, the set-membership filtering problem has received extensive research interests due to its engineering significance to estimate a set which includes the true state of the system rather than a single vector. What's more, the communication protocol has been widely applied in the control systems because of its ability to prevent from data collisions and reduce the burden of the network. From the engineering practice, it is of vital importance to investigate the set-membership filtering under communication protocols. In this paper, a bibliographical review is provided on the set-membership filtering for networked control systems (NCSs) under communication protocols. Next, the concept of the NCS is briefly introduced. Some recent advances on the set-membership filtering problem for NCSs are summarized. Then, some well-known scheduling schemes are presented and the results of the set-membership filtering for NCSs under communication protocols are reviewed. Finally, some concluding remarks are given and some potential future research directions are pointed out.